PRC1 and RACGAP1 are Diagnostic Biomarkers of Early HCC and PRC1 Drives Self-Renewal of Liver Cancer Stem Cells - Liao, Shixin; Wang, Kaili; Zhang, Lulu; Shi, Gaoli; Wang, Zhiwei; Chen, Zhenzhen; Zhu, Pingping; He, Qiankun (Frontiers in Cell and Developmental Biology, 2022)
Hepatocellular carcinoma (HCC) is the fourth leading cause of cancer-related deaths across the world. Due to the lack of reliable markers for early HCC detection, most HCC patients are diagnosed in middle/late stages. Liver cancer stem cells (CSCs), which are drivers of liver tumorigenesis, usually emerge in the early HCC stage and are also termed as liver tumor initiation cells (TIC). Liver CSCs contribute to initiation, propagation, and metastasis of HCC and also play a key role in tumor therapy. Taking advantage of online-available data sets, bioinformatic analyses, and experimental confirmation, here we have screened out PRC1 and RACGAP1 as reliable markers for early HCC detection. PRC1 or RACGAP1 knockdown dramatically inhibited the proliferation, migration, and invasion capacities of HCC cells, conferring PRC1 and RACGAP1 as predominant modulators for HCC propagation and metastasis. Moreover, the sphere formation capacity of HCC cells was impaired after PRC1 knockdown, revealing the function of PRC1 as a modulator for liver CSC self-renewal. Furthermore, the inhibitor of PRC1 had same phenotypes as PRC1 knockdown in HCC cells. Altogether, PRC1 and RACGAP1 are identified both as prognosis markers for early HCC detection and therapeutic targets for liver cancer and liver CSCs, adding additional layers for the early prognosis and therapy of HCC.